(untitled) (Psicologia USP, 2014)
Morphological awareness refers to the ability of reflecting on the smallest units of meaning in a language and in using them intentionally in word structuring and recognition. In this study arguments are presented to support the idea that in Portuguese, as in other alphabetic languages​​, morphological awareness contributes to both reading comprehension and for orthographic performance. The participants were 72 students from 3rd through 5th grades in a Public School (Curitiba, Brazil), divided in two groups (for each grade) according to orthographic performance. The data collection involved the application of seven assessment tools, as follows: one for spelling, three for morphological awareness and two for reading comprehension. The analysis of empirical data shows that performance in the morphological awareness assessment tasks (inflectional and derivational) contributes significantly to explain the variance in the performance of the participants for both reading comprehension and orthographic writing.